PHYTOCHEMICAL AND ETHNOPHARMACOLOGICAL REVIEW OF HETEROPYXIS NATALENSIS - MAROYI, ALFRED (Asian Journal of Pharmaceutical and Clinical Research, 2019)
The bark, leaves, roots, and twigs of Heteropyxis natalensis are widely used as herbal medicines in Southern Africa. The aim of this study was to review the phytochemical and ethnopharmacological properties of H. natalensis so as to provide baseline data required for evaluating the therapeutic potential of the species. Information on the botanical profile, medicinal uses, phytochemistry, and pharmacological properties of H. natalensis was undertaken using databases such as ScienceDirect, SciFinder, PubMed, Google Scholar, Medline, SCOPUS, EThOS, ProQuest, OATD, and open-thesis. Pre-electronic literature of conference papers, scientific articles, books, book chapters, dissertations, and theses were carried out at the university library. Literature search revealed that H. natalensis is used as an aphrodisiac, anti-infection, blood purifier, decongestant, for weaning, ethnoveterinary medicine and as herbal medicine for bleeding disorders, gums, nose, colds, gum infections, impotence, menorrhagia, respiratory disorders, toothache, and wounds. Phytochemical compounds identified from the species include essential oils, 3β-hydroxylup-20(29)-en-28-al, (E)-1-(2’,4’-dihyroxy,5’- methoxy,3’-methylphenyl)-3-phenylprop-2-en-1-one, (2E)-2-[(2E)-1-hydroxy-3-phenylprop-2-en-1-ylidene]-5-methoxy-6,6-dimethylcyclohex-4-ene- 1,3-dione, 2’,4’-dihydroxy-6’-methoxy-3’,5’-dimethylchalcone, 3’,4’,5’-tri-O-methyl-3,4-methylenedioxy ellagic acid, 3,5,7-trihydroxyflavan, 5-hydroxy- 7-methoxy-6-methylflavanone, aurentiacin A, betulinic acid, cardamomin, lupenone, lupeol, quercetin, and sitost-4-en-3-one. Pharmacological studies revealed that H. natalensis extracts and compounds have antibacterial, antimycobacterial, antifungal, antioxidant, anti-inflammatory, cytotoxicity, and pro-inflammatory activities. Detailed studies are required to establish the efficacy, clinical relevance, safety and mechanisms of action of the plant extracts, and compounds of H. natalensis.